2001
DOI: 10.1021/jp0030084
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Carbohydrate Aqueous Solutions. Dielectric Relaxation as a Function of Glucose and Fructose Concentration

Abstract: At some solute concentrations c between 1 and 5.4 mol/L, the complex (electric) permittivity of aqueous solutions of D-glucose and D-fructose has been determined as a function of frequency υ between 300 kHz and 40 GHz. The permittivity spectrum of the 5.4 mol/L D-fructose solution has been measured at six temperatures between 10 and 35 °C, and the other spectra have been taken at 25 °C. All dielectric spectra revealed one dispersion/dielectric loss region, which indicated a rather homogeneous relaxation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 41 publications
5
109
1
Order By: Relevance
“…Thus, we can claim that variations in glucose concentration even at low values such as physiological ones should directly affect the dielectric properties of a solution, independently from other mechanisms that may be induced by glucose variations. On the other hand, it is confirmed that the impedance variations due to variations in glucose are certainly more evident at low frequencies, and this may partially explain why they were not observed in the studies [22,23] where frequencies over 1 MHz were considered.…”
Section: Accepted M Manuscriptmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, we can claim that variations in glucose concentration even at low values such as physiological ones should directly affect the dielectric properties of a solution, independently from other mechanisms that may be induced by glucose variations. On the other hand, it is confirmed that the impedance variations due to variations in glucose are certainly more evident at low frequencies, and this may partially explain why they were not observed in the studies [22,23] where frequencies over 1 MHz were considered.…”
Section: Accepted M Manuscriptmentioning
confidence: 79%
“…In [2] it was claimed that these effects are entirely responsible for the impedance variation of blood and underlying tissues, since glucose variations do not directly affect the dielectric properties of the investigated medium in the MHz band, as also stressed in other studies from the same research group [20,21]. In fact, some references were provided to other studies where the effect of variations in glucose concentration was studied in water [22,23]. In [23] it was shown that at glucose concentrations lower than 1 g/cc the dielectric properties of the glucose-water solution are not different from those of pure water.…”
mentioning
confidence: 89%
“…As a result, the hydrogen bonds between water molecules in the primary solvation shell and water molecules outside the shell are disrupted, thus weakening hydrogen bonding structure of the water just beyond the solvation shell (Gallina et al, 2006;Paolantoni et al, 2007). However, despite the weakening of hydrogen bonds in water outside the solvation shell, the strong hydrogen bonding between glucose moieties of cerebrosides and water molecules in the first solvation shell increases the viscosity of the water and potentially slows the rate of water permeation through the SC (Fuchs and Kaatze, 2001;Comesaña et al, 2003).…”
Section: Lipidsmentioning
confidence: 99%
“…[29,32] At n 3 GHz the wavelength of the electromagnetic field within the sample was sufficiently large to allow for quasi-static approaches. Therefore, in this frequency range, input impedance measurements have been performed using specimen cells of the cut-off variety.…”
Section: à4mentioning
confidence: 99%
“…The temperature of the specimen cells was controlled to be within 0.05 K and it was measured with an error of less than 0.02 K. [29,32] Auxiliary Measurements: The density 1 of the carbohydrate solutions has been measured with a pycnometers (20 mL, 25 mL, D1/ 1 = 0.002) that had been calibrated against distilled and degassed water. The shear viscosity h s of the samples has been determined to within 2 % using a falling ball viscosimeter and a set of Ubbelohde capillary viscosimeters.…”
Section: à3mentioning
confidence: 99%